2012
DOI: 10.1038/emboj.2011.493
|View full text |Cite
|
Sign up to set email alerts
|

ATR maintains select progenitors during nervous system development

Abstract: The ATR (ATM (ataxia telangiectasia mutated) and rad3-related) checkpoint kinase is considered critical for signalling DNA replication stress and its dysfunction can lead to the neurodevelopmental disorder, ATR-Seckel syndrome. To understand how ATR functions during neurogenesis, we conditionally deleted Atr broadly throughout the murine nervous system, or in a restricted manner in the dorsal telencephalon. Unexpectedly, in both scenarios, Atr loss impacted neurogenesis relatively late during neural developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 87 publications
5
94
0
Order By: Relevance
“…9). These results are in agreement with the reported requirements for p53 in the apoptotic death of neural progenitors with abnormal cell cycle progression induced by p57 Kip2 or Atr inactivation 42,43 . In fact, p53 loss has been shown to exacerbate the effects of DNA replication defects in several models [44][45][46] , further supporting the idea that the primary defect in Cdh1-deficient cells is related to abnormal DNA replication.…”
Section: Discussionsupporting
confidence: 93%
“…9). These results are in agreement with the reported requirements for p53 in the apoptotic death of neural progenitors with abnormal cell cycle progression induced by p57 Kip2 or Atr inactivation 42,43 . In fact, p53 loss has been shown to exacerbate the effects of DNA replication defects in several models [44][45][46] , further supporting the idea that the primary defect in Cdh1-deficient cells is related to abnormal DNA replication.…”
Section: Discussionsupporting
confidence: 93%
“…In this model, the severe loss of neurons throughout the cerebellum, hippocampus and cortex correlates with areas of neurogenesis in the developing brain, with cell death arising from replication stress in the absence of ATR activity [56]. Similarly, a brain-specific ATR knockout suggested that ATR signalling in the brain is critical during rapid waves of neuroprogenitor cell division in the GE and cerebellum at late stages of development [57]. Other mutant proteins, such as pericentrin and MCPH1 have been implicated in the cause of microcephaly through coupling ATR signalling to the G2/M checkpoint via the centrosome [58,59].…”
Section: Atr and Atr-seckel Syndromementioning
confidence: 88%
“…CGNPs are highly sensitive to apoptosis in response to genotoxic stress (Chong et al, 2000;Lee et al, 2012). The mitotic abnormalities in Aspm-deficient CGNPs, and prior studies demonstrating a role for Aspm in mitotic spindle dynamics (Zhong et al, 2005;Fish et al, 2006;Higgins et al, 2010) and DNA repair (Kato et al, 2011) suggest that increased CGNP apoptosis in Aspm mutants might be caused by increased DNA damage.…”
Section: Aspm Deficiency Increases Progenitor Dna Damage and Apoptosismentioning
confidence: 97%